Acceptability and efficacy of the culturally adapted problem management plus intervention for people with disability in Pakistan: a pilot cluster randomized controlled trial - Hussain, Basharat; Khalily, Muhammad Tahir; Waqas, Ahmed; Rahman, Atif; Angelakis, Ioannis; Nisar, Anum; Zaman, Sabir; Akhtar, Tanveer (Frontiers in Psychiatry, 2025)
BackgroundIn Pakistan, the mental health care for persons living with disabilities is insufficient, lacking a holistic approach to address their needs. This research evaluates the adapted PM+’s (IA-PM+) initial efficacy and acceptability in improving mental health among persons living with disabilities, contributing to the integration of mental health services within primary care settings in Pakistan.MethodsThis study employed a two-arm, single-blind cluster randomized controlled trial in a community setting within Union Council Kuri Dolal, Tehsil Gujjar Khan, District Rawalpindi-Pakistan. It compared an Active Treatment group, receiving five sessions of the IA-PM+ intervention, against a Delayed Treatment Control group. A total of 148 participants were randomized. Randomization occurred at the village level, with clusters assigned to either the intervention or control group. The intervention’s effectiveness and participant satisfaction were assessed using a variety of measures, including the GHQ-12, WHODAS 2.0, DASS-21, and the Client Satisfaction Questionnaire, at baseline, the 8th week, and during a 3-month follow-up. Qualitative feedback was gathered at the end of the study to assess the intervention’s acceptability among the participants.ResultsThe study achieved a 100% retention rate. Baseline demographics showed a majority male participation with a variety of disabilities predominantly lower limb. Significant improvements were noted in the intervention group across WHODAS scores (Cohen’s d= 0.66), PTSD symptoms (d= 0.75), and DASS scores for depression (d= 0.46), anxiety (d=0.65), and stress (d= 0.47). Similar trends were noted during the follow-up phases. However, life satisfaction scores initially higher in the control group evened out by follow-up, and perceived social support was consistently lower in the intervention group. High levels of client satisfaction were reported in the intervention group, with most participants finding the sessions beneficial and expressing willingness to recommend the service to others. The qualitative interviews revealed that the integration of religious practices, such as associating stress management techniques with Adhan, significantly enhanced the acceptability of the culturally adapted PM+ intervention. Participants reported that this cultural alignment made the coping strategies more relatable and easier to adopt, contributing to improvements in both their mental health and somatic symptoms.Clinical Trial Registrationhttps://clinicaltrials.gov/ct2/show/NCT04981522, identifier NCT04981522.